Politik Pemerintah Malaysia dalam Membatasi Kebergantungan pada Pekerja Konstruksi Asing Indonesia - Helmi, Rahmadhona Fitri (Fakultas Ilmu Sosial Universitas Negeri Padang, 2013)
Malaysian government's dependence on foreign workers, parti-cularly in the construction sector, raises concerns from many quarters, both from the Malaysian government and people of Malaysia themselves. It is evident from the number of foreign workers who migrated to Malaysia in search of work area. One of the workers who migrated to Malaysia are workers from Indonesia. Increasing the number of Indonesian workers to Malaysia from year to year due to many factors, such as geographical, historical, and cultural factors. But, on the other side, the entry of foreign workers into Malaysia sparked the emergence of a variety of problems. As a result, Malaysian government try to implement various efforts to overcome the problems posed by foreign workers, especially from Indonesia. However, the efforts have not been able to achieve a satisfactory and significant results. Kata Kunci: Kebergantungan, pekerja asing, konstruksi